How to be brave like a snail - Hrab, Naseem (Hrab, Naseem. Snail & Stump, 2025)
Snail and his friend Stump, learn about courage, friendship, and emotional honesty. When Snail enters a paper airplane contest with Stump's encouragement, he must overcome his own fears of failure and asking for help. After the contest, Snail supports Stump as he copes with disappointment. Together, they learn to express their feelings and strengthen their friendship through understanding and communication.